ANALISIS PENGARUH KOMPENSASI, KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU DI MADRASAH TSANAWIYAH NEGERI 1 KOTA TANGERANG SELATAN - Rahmayanti Tumanggor (Universitas Pamulang, 2018)
The purpose of this research was to know about the effect of Compensation, Competence and Motivation to the Teacher’s Performance in Madrasah Tsanawiyah Negeri 1 South Tangerang City, whether partially or simultaneously.This research used quantitative research method which was descriptive analysis. The population in this research were 63 Teachers in Madrasah Tsanawiyah Negeri 1 South Tangerang City. The samples also used 63 Teachers. The using of Sampling Technic was Teknik Sampling Jenuh. The Data Analysis Plan in this research was Descriptive Statistic Test, Data Quality Test, Regression Analysis, and Hypothesis Test.Based on Data Analysis Plan which was used, then here there were some results:There was negative and significant effect between compensation and Teacher’s performance based on regression coefficient value of compensation variable (β1) that was negative (-0.015), and compensation variable had tcount -0.211 little than ttable 1,670 or compensation variable had significant level 0,834 bigger than 0,05. It means that rejected Ha1 and accepted Ho; that compensation effected negatively and did not significant partially to the Teacher’s performance.There was positive and significant effect between competence and Teacher’s performance based on regression coefficient value of competence variable (β2) that was positive 0,279, competence variable had tcount 2,093 bigger than ttable 1,670 or competence variable had significant level 0,041 little than 0,05. It means that accepted Ha2 and rejected Ho; that competence effected positively and significant partially to the Teacher’s performance.There was positive and significant effect between motivation and Teacher’s performance based on regression coefficient value of motivation variable (β3) that was positive 0,30, motivation variable had tcount 3,113 bigger than ttable 1,670 or motivation variable had significant level 0,003 little than 0,05. It means that accepted Ha3 and rejected Ho; that motivation effected positively and significant partially to the Teacher’s performance.There was positive and significant effect between compensation, competence, and motivation simultaneously to the Teacher’s performance, that was Fhitung 8,374 bigger than Ftable was 2,370 or significant level 0,000 little than 0,05. So it accepted Ha4and rejected Ho, then it can be assumed that compensation, competence, and motivation effected significant simultaneously to the Teacher’s performance.From this research it can be assumed that compensation, competence, and motivation variable effected significant simultaneously to the Teacher’s performance.Keywords : Compensation, Competence, Motivation, and Teacher’s Performance